CORPORATE AI ADOPTION AND FINANCIAL RISK: THE MEDIATING ROLE OF CASH HOLDING BEHAVIOR - Umar Abduloh; Sri Wahyuni (JAT : Journal Of Accounting and Tax, 2026)
This study aims to analyze the effect of Artificial Intelligence (AI) adoption on corporate financial risk by considering the mediating role of cash holding behavior. The study employed a quantitative approach using secondary data derived from annual reports of non-financial companies listed on the Indonesia Stock Exchange during 2022–2024. The sample was selected using purposive sampling, resulting in 33 companies with 99 observations. AI adoption was measured using annual report text analysis, financial risk was proxied by stock return volatility, while cash holding behavior was measured using the ratio of cash to total assets. Data analysis was conducted using panel data regression with the Common Effect Model (CEM) and mediation testing. The findings reveal that AI adoption has not directly reduced corporate financial risk. However, AI adoption positively affects corporate cash holding behavior. Furthermore, cash holding behavior significantly reduces corporate financial risk. Nevertheless, cash holding behavior is unable to mediate the relationship between AI adoption and corporate financial risk. These findings indicate that AI implementation has not been fully integrated into corporate financial risk management. This study contributes to the literature on corporate AI and corporate financial policy in the context of developing countries.